Eccentric Connectivity Index of Some Special Molecular Graphs and Their R-Corona Graphs - Gao, Yun; Liang, Li; Gao, Wei (International Journal of Chemical and Process Engineering Research, 2014)
In this paper, we determine the eccentric connectivity index and augmented eccentric connectivity index of fan graph, wheel graph, gear fan graph, gear wheel graph and their r-corona graphs.